Demonstrating the antinociceptive action of renin-angiotensin system modulators in mice - R. N. RUSU; Daniela C. ABABEI,; Gabriela D. STANCIU; A. LUCA; R.I. POPESCU; Veronica BILD (Medicamentul Veterinar)
Research done in the present study belongs to a wider area of experimental determinations on nociception models, when using laboratory animals. Their aim is to determine the ED50 value (Efficient dose 50) in conditions of inflammatory (chemical stimulus) and non-inflammatory (thermic stimulus) antinociception of some renin-angiotensin system modulators: captopril, ramipril, candesartan. The experimental determinations were realized accordingly to bioethical regulations concerning laboratory animals. The study has used Swiss mice, weighing between 20-30g, being held in constant temperature (21°C ± 2°C) and a dark / light cycle of 12 hours (7.00 AM / 7.00 PM). The researched substances are administered as CMC-Na 0.1% suspensions in geometrical progression doses. The following nociception models have been used: abdominal constrictive response test, hot plate test, formalin test. The abdominal constrictive response test has been evaluated as quantal, the hot plate test and the formalin test have been interpreted as gradual. The regression line, the correlation coefficient and the interval of trust for each substance and studied model have been analyzed. The obtained ED50 values are compared to each other to evaluate the potency of the substances for each nociception model. The obtained data is used for realizing fixed-ratio antinociceptive combinations.